Implikasi Pemahaman Perpajakan terhadap Kepatuhan Pelaporan SPT Tahunan PPh 21 - Hanunah Nafi’iyah; Oktavia Aulia Rizki; Muhammad Saddam Najib Ibrahim (MASALIQ, 2025)
This study is motivated by the low compliance rate in the reporting of Annual Income Tax Returns (SPT) for Article 21 Income Tax (PPh 21), often attributed to taxpayers’ limited understanding of tax procedures, regulations, and obligations. The objective of this research is to analyze the implications of tax knowledge on compliance with PPh 21 annual reporting. A descriptive qualitative method was employed, with data collected through interviews and observations involving individual taxpayers. The findings reveal a significant gap in tax understanding among taxpayers, which directly affects their compliance levels. The study confirms a strong correlation between the level of tax knowledge and reporting compliance—higher awareness of tax rights and obligations leads to greater compliance. Therefore, increasing the frequency and quality of tax education and outreach is identified as a strategic approach to improving taxpayer compliance. The implications of this study highlight the importance of education-based strategies in tax administration policies and offer recommendations for further research with broader sample coverage and more diverse methodological approaches.